Prioritas Risiko Keselamatan dan Kesehatan Kerja pada Tahap Assembly Pembangunan Kapal Menggunakan Metode Failure Mode and Effects Analysis (FMEA) - Hery Indria Dwi Puspita; Mohammad Farezi Rachmadani; Gandu Eko Julianto Suyoso (ARTERI : Jurnal Ilmu Kesehatan, 2026)
Shipbuilding consists of three main stages: fabrication, assembly, and erection. The assembly stage involves fit-up, welding, and weld grinding (finishing), each of which poses occupational safety and health risks to shipyard workers. This study aimed to analyze Occupational Safety and Health (OSH) risks in the shipbuilding process at PT XYZ, with a primary focus on the assembly stage using the Failure Mode and Effects Analysis (FMEA) method. Supporting data were collected through interviews with the project supervisor directly involved in all assembly activities, as well as field observations of the work environment and workers. Risk assessment was conducted by evaluating three key parameters—Severity, Occurrence, and Detection—to calculate the Risk Priority Number (RPN) for each identified hazard. The results identified 14 potential occupational hazards across five assembly work activities. The assembly stage was predominantly characterized by moderate-risk hazards. The most critical risk identified was noise-induced hearing loss caused by grinding machine noise during the weld grinding process, with an RPN of 216. In addition, electrical burns resulting from damaged welding cables and thermal burns caused by welding spatter each recorded an RPN of 210, both of which were also classified as moderate-risk hazards. The recommended risk control measures include strengthening administrative controls through regular toolbox meetings to enhance workers' awareness of the hazards associated with permanent hearing loss, accompanied by mandatory use of appropriate personal protective equipment (PPE), including earplugs or earmuffs, coveralls, safety helmets, and safety footwear. These recommendations are expected to minimize occupational accidents and improve the Occupational Safety and Health Management System (OSHMS) at PT XYZ